Influence of a net cage tilapia culture on the water quality of the Nova Avanhandava reservoir, São Paulo State, Brazil - doi: 10.4025/actascibiolsci.v34i3.7298 - Margarete Mallasen; Helenice Pereira de Barros; Daniela Polizeli Traficante; André Luiz Scarano Camargo (Acta Scientiarum. Biological Sciences, 2012)
In order to understand the influence of a net cage tilapia culture on the environment, water quality parameters were investigated during the period between December, 2005 and November, 2007. Three sampling stations were established in the reservoir of Nova Avanhandava (Zacarias, São Paulo State) as follows: upstream of net cage area (P1), in the rearing place (P2) and downstream of net cage area (P3). The mean values of the parameters examined in the water sampling stations were within the standards of water quality recommended by resolution no. 357/2005 of the Conselho Nacional do Meio Ambiente for class 2 freshwater bodies. A significantly higher mean concentration of total phosphorus (p < 0.05) in the P2 (0.035 mg L-1) was the result of the uneaten feed and feces of fish. The average concentration of total phosphorus in P3 was lower (0.015 mg L-1), which was assimilated by the aquatic ecosystem. The frequent monitoring of the water parameters is fundamental, so the producer can adjust the management according to environmental conditions, by reducing fish density or changing feeding rates for example, to mitigate or avoid water quality deterioration.